PELAKSANAAN BUDAYA PERKAWINAN PITU POLE MASYARAKAT SUKU TAJIO KASIMBAR SULAWESI TENGAH DALAM PERSPEKTIF FILOSOFI PENDIDIKAN ISLAM - Hamlan Andi Baso Malla (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
This study discusses the implementation of maritime culture pitu pole Tajio Kasimbar community, Central Sulawesi in the perspective of Islamic educational philosophy using the approach of Islamic education philosoph. The research used qualitative method with observation data collection technique, non structure interview and document search. Data analysis techniques through data reduction, display data, data verification to generate conclusions and findings of research results. The results of this study indicate that the implementation of the marriage culture pitu pole derived from the acculturation of Mandar culture and Tajio culture with the implementation stage, namely; Adat Meduta, Inviting Inviting Process, Te Boting Mongon, Melontibi, Mengesuro, Mongulung Te Pecinde, Submission and Admission of Indigenous Delivery, Barzanji Readings, Monikah Custom, Mopaende. Monyalama Implementation of adat is seen from the aspect of Islamic education philosophy has a theological meaning that affects the personality of the Tajio tribe in maintaining the value of brotherhood, kinship, and Islamic personality in performing worship to Allah SWT